Evaluation of prosthodontic complications in screw-retained and cement-retained crowns in dental implants: An original research - Mansi Rajput; Arshdeep S Kohli; Hina N Abdul; Sunpreet K Sandhu; Radhika Thakkar; Shivani Karre (Journal of Pharmacy and Bioallied Sciences, 2024)
Aim: Single-tooth implant restorations, whether screw-retained or cement-retained, are essential for prosthodontic rehabilitation despite having low design flexibility, cosmetic appeal, and high 5-year survival rates. Materials and Methods: A study involving 14 patients with missing mandibular first molars used 28 implants and cement-retained and screw-retained prostheses. Patients had a single edentulous gap, adequate dental hygiene, and sufficient bone volume at the implant site. The study adhered to the Helsinki Declaration, followed WHO 2007 safety guidelines, and evaluated soft tissue, bone height, and bone loss. Data analysis included the Student's t-test and Mann–Whitney U-test. Results: In patients between the ages of 17 and 46, single-implant restorations were compared with cement- and screw-retained at 6 months. Abutment screw loosening and peri-implant soft-tissue traits did not differ significantly from one another. Conclusion: The study compared screw- and cement-retained implant restorations in 28 single-tooth implant-supported prostheses over a 6-month functional loading period, finding no significant improvement in either approach.